STUDY OF CALCULATION OF RUNAWAY DISCHARGE INTO EFO SETTLING POND AT PT GAG NIKEL, SOUTHWEST PAPUA PROVINCE: KAJIAN PERHITUNGAN DEBIT LIMPASAN YANG MASUK PADA SETTLING POND EFO DI PT GAG NIKEL PROVINSI PAPUA BARAT DAYA - Wopari, Felice Deglardini; Ginting, Fandi Arapenta; Hajijah, Fajrianti Nur; Tandy, Lia Medy (Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2025)
Settling Pond EFO is one of the mine water management facilities managed by PT Gag Nikel, functioning as a water reservoir and sedimentation deposition site. This study evaluates the suitability of the Settling Pond EFO capacity to the incoming runoff discharge, especially in high rainfall conditions. Based on the analysis results, the runoff discharge entering the Settling Pond EFO reached 0.42 m³/second, with a catchment area of ​​0.188 km² and a rainfall intensity of 10.54 mm/hour. The evaluation showed three main findings: (1) There is a change in volume between the initial design of the pond and the actual conditions due to long-term use; (2) The Settling Pond EFO has the potential to be full if it rains for 11 hours; and (3) The Settling Pond capacity has not been optimally utilized, with the remaining unfilled volume of 1,636.90 m³. These results indicate the importance of optimizing the capacity and management of the Settling Pond to overcome the risk of excess runoff.